Blood cell counts can predict adverse events of immune checkpoint inhibitors: A systematic review and meta-analysis - Zhou, Juyue; Du, Zhonghai; Fu, Jie; Yi, Xiuxiu (Frontiers in Immunology, 2023)
Background: Cancer has been widely concerned because of its high mortality rate, and how to prolong life has become the focus of attention. In recent years, immune checkpoint inhibitors(ICIs) as new antitumor drugs have achieved good clinical efficacy, however, their adverse effects have also been exposed in the process of application. In order to clarify the predictors of adverse effects, scientists have conducted a series of studies. Blood counts have been shown to be potentially monitorable risk indicators associated with the occurrence of immune checkpoint inhibitors adverse events(irAEs), and a meta-analysis was performed to further clarify the guiding significance of blood counts in the clinical setting. Methods: Studies that satisfied the inclusion criteria were obtained by searching the database. Included studies were those in which irAEs had occurred and in which evidence of an association between blood counts and irAEs was reported. The included ones were evaluated for quality, and a meta-analysis was performed using the odds ratio (OR) and 95% confidence interval for each study, in addition to sensitivity analysis and subgroup analysis. Results: A total of 20 articles were included in our study. The analyses were performed separately according to different blood cell count indicators. The blood cell count metrics associated with immunotoxicity were: absolute eosinophil count, neutrophil: lymphocyte ratio, and platelet: lymphocyte ratio. Conclusion: Our review and meta-analysis of retrospective studies suggest that absolute eosinophil count, neutrophil: lymphocyte ratio, and platelet: lymphocyte ratio may serve as predictors of the emergence of irAEs. Given the small number of studies focusing on the relationship between patient blood cell levels and the risk of irAEs, future studies need to further explore the mechanisms of occurrence and potential associations.